Corporate social responsibility disclosure and financial performance - Tran, Nguyen T. (Economic and business review, 2025)
This study examines the relationship between corporate social responsibility (CSR) disclosure and firm performance, with particular attention to CSR’s role as a mitigating mechanism during periods of economic crisis, notably the COVID-19 pandemic. Utilizing a unique hand-collected dataset comprising CSR disclosures from Vietnamese publicly listed firms in the VNR500 index between 2014 and 2021, the analysis employs both accounting-based (return on equity) and market-based (Tobin’s Q) performance indicators. The empirical findings indicate a positive association between CSR disclosure and firm performance across both measures. Disaggregated analysis reveals that governance-related disclosures significantly enhance market valuation, whereas the presence of a well-articulated CSR vision and strategic orientation correlates positively with accounting profitability. These results suggest that robust governance frameworks, environmental stewardship, and socially responsible product strategies contribute to superior firm outcomes. Moreover, the study provides empirical support for the conceptualization of CSR as an insurance like mechanism that mitigates the adverse effects of external shocks—such as the COVID-19 pandemic—by preserving firm value and protecting shareholder interests.
Keywords: business efficiency; družbena odgovornost; enterprises; pandemic; pandemija; podjetje; social responsibility; uspešnost poslovanja; Viet Nam; Vietnam